Urethral mucosal prolapse in young girls: A report of nine cases in Cotonou - Fiogbe M; Hounnou G; Koura A; Agossou-Voyeme K (Wolters Kluwer Medknow Publications, 2011)
Background: Urethral mucosal prolapse is rare. This condition may be confused with tumour or sexual abuse in girls. This study aims at reporting the pathology presentation and therapeutic options of urethral prolapse in girls. Materials and Methods: A retrospective study was undertaken from January 2000 to December 2008. Authors analysed the clinical features and the treatment options. Results: There were nine cases of urethral prolapse. The ages ranged from 2.5 to 10 years (mean age: 5.08 years). The main presentation was vaginal bleeding (five cases). Physical examination revealed a soft, non-tender mass that bleeds on touch (six cases), with a length ranging from 0.75 to 1 cm. Urine culture in four patients revealed urinary infection that yielded Escherichia coli in three cases and the Staphylococcus aureus in one case. Six patients had surgical treatment while three had medical treatment. In those who had surgery, one had acute urine retention and one had recurrence that was treated successfully without operation. All the nine girls are cured. Conclusion: Urethral prolapse is a disease of the prepubertal girls of low socio-economic group. Diagnosis is clinical. The treatment of choice is surgical.